Beyond Realism - Theatre Pedagogy in Philippine Universities - Fernandez, Steven Patrick (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Universities lead in Philippine theatre practice now. As the majority of viewers are the students filling up large sections of venues, arriving in droves, and making producers realize this audience’s potentials, the academe shapes the appreciation of theatre. Theatre will therefore thrive, survive, and be popularized in the universities. Our schools will have the resources and motivations to nurture theatre goers. The universities ignite an interest easily because study inherently breeds curiosity, inquisitiveness, the power to express, and the exploration to discover how meanings may be shown in many alternative ways. In the university, methods are studied and pedagogies are developed. The universities become the breeding grounds of new works that will eventually swell the ranks of our audiences. Because of these factors, innovation in theatre will evolve an audience that will spill into the mainstream of live performance. This condition should subsequently challenge the movies and TV as alternative (and intelligent) means of entertainment.